Effect of School Environment on Children’s Health in Government and Private School in Agra City. - Singh, Dr .Deepti; Singh, Dr.Manoj Kumar (JOURNAL OF INDUSTRIAL RELATIONSHIP CORPORATE GOVERNANCE AND MANAGEMENT EXPLORER, 2022)
Government school students have more health problems than the private school. Government schools don't have the standard classrooms, adequate sports facilities, safe drinking water, and adequate light and ventilation in place, when compared to private schools. The government school has limited budget and resources when compared to private school. Most of the lower and lower middle class family children are studying in government school. The government should apportion special budgets to the government schools, for the allocation of resources and facilities such as good ventilation, limited students numbers per class, and more awareness among teachers and parents.Among the government school, majority of the respondents were found healthy( 74.47%) but private school, majority of the respondents were found healthy (77.36%). It means healthy children in private school is more than the government school.Last but not the least, these types of programs will be helpful in preventing, or at least minimizing, environmental health hazards. Keywords: School, Environment, Health, Government, Children.